The Safe Standing movement in English football: Mobilizing across the political and discursive fields of contention. (November 2022) - Turner, Mark
Twenty-eight years after the Taylor Report into the Hillsborough disaster recommended that all football grounds in the top two divisions in England and Wales should become all-seated, the UK government, in 2018, announced a review into the safety of modern standing areas and whether developments in stadium safety might justify changing the all-seating legislation to permit Safe Standing. These events are the outcome of a 30-year social movement in which a critical mass of supporters, through the relational networks they formed, have built collective action. Drawing upon both archival and fieldwork research to analyse the longer-term impact which all-seated stadia have had on football supporters' consumption of the game in England, the article uses relational sociology to tell the story of the movement, and studies the working tactics and structure of a small network mobilizing across the political and discursive fields of contention post-Hillsborough. It argues that whilst now a more effective movement with technological and political capital, Safe Standing continues to raise important questions around the historical views on football fans as somehow deviant and reinforces the long-term impact and legacy of Hillsborough on supporters' modern cultural consumption of the game by moving within the parameters of the all-seating legislation.